Influência da turbulência intermitente na estimativa dos fluxos de CO2 noturnos - Santos, Diego Jatobá dos (2012)
Nocturnal turbulent flux data are analysed, initially for two experimental sites in Brazil, and later for a large variety of biomes. In such case, a wide dataset, originated from more than a hundred flux stations scattered over Europe and the Americas is used. Emphasis is given to important aspects associated to the occurrence of intermittent turbulence and its implications for CO2 nocturnal flux estimates. Intermittency factors (IF) for CO2 and sensible heat fluxes are determined for the set of stations. In most cases, there was agreement between the results for CO2 and sensible heat, specially for those stations that were less intermittent, on average. A larger number of stations showed low IF for CO2 than for sensible heat fluxes. CO2 flux intermittency was significantly larger over higher canopies than over savannas or crops, while the same difference is smaller for the sensible heat flux. An investigation on the CO2 flux dependence on the temporal variability of the turbulence intensity is carried on . The main purpose of such an anlysis is identifying whether ther is CO2 storage during low turbulence periods and if such accumulated CO2 affects the fluxes in subsequent periods. In the vast majority of the stations, the classical pattern of NEE decreasing as u* tends to zero is observed. The hypothesis of the present study is that such NEE decrease under calm situations does not necessarily imply on flux lost by the eddy covariance technique, but that it may have not been properly captured by the CO2 storage term, being later measured in subsequent turbulent situations. Therefore, the present study has as the main goal identifying a potential problem in the correcting procedure commonly applied for low turbulent periods. Specifically, it is important to analyse whether the periods whose data are being replaced are not suceeded by others for which there is flux excess, characterizing, therefore, an excessive correction. Results indicate that there is a large quantity os stations for which the fluxes are independent on turbulence intensity variability, with evidences that the observed reduction during calm periods is compensated when it gets turbulent. In such cases, it is possible that corrections commonly used for calm conditions are, indeed, excessive. .